2017
DOI: 10.1371/journal.pone.0175887
|View full text |Cite
|
Sign up to set email alerts
|

Southern Tunisia: A still high endemicity area for hepatitis A

Abstract: BackgroundHepatitis A (HAV) and E (HEV) viruses are responsible for enterically transmitted hepatitis. Tunisia is reported to be of intermediate endemicity for HAV and of low seroprevalence for HEV; however, data from rural areas of South Tunisia are lacking.MethodsSera from 216 asymptomatic pregnant women and from 92 patients with acute hepatitis were collected between October 2014 and November 2015. Total and IgM anti-HAV immunoglobulins and anti-HEV IgG and IgM were investigated. Anti-HAV IgM-positive sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…6 In a study conducted among acute hepatitis patients at Kenyatta National Hospital in Nairobi, Kenya, it was found that all those positive for anti-HAV and anti-HEV antibodies used pit latrines in their households. 16 This has been also reported previously in Northern Africa and elsewhere. 18 Hepatitis A virus is spread through food and water contaminated by the feces of people infected with hepatitis A virus.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…6 In a study conducted among acute hepatitis patients at Kenyatta National Hospital in Nairobi, Kenya, it was found that all those positive for anti-HAV and anti-HEV antibodies used pit latrines in their households. 16 This has been also reported previously in Northern Africa and elsewhere. 18 Hepatitis A virus is spread through food and water contaminated by the feces of people infected with hepatitis A virus.…”
Section: Discussionsupporting
confidence: 84%
“…These results are in agreement with what has been reported in south Tunisia in 2017 and elsewhere. 16 Improvement in hygienic and good sanitation practices would reduce the transmission of the virus from person-to-person. On the contrary, developed countries are characterized by low antibody seroprevalence of HAV during childhood.…”
Section: Discussionmentioning
confidence: 99%
“…All clinical HAV strains from different regions of Sfax Governorate belonged to genotype IA [10]. This result is in an agreement with those of other Tunisian studies, which demonstrated that the predominant genotype still continues to be IA [15][16][17]. In addition, HAV sequences were closer to GBM reference strain (isolated in Germany) than to Asian sequences, suggesting a close genetic relatedness with HAV strains isolated in Mediterranean countries.…”
Section: Molecular Epidemiology Of Hepatitis a Virus Infectionsupporting
confidence: 85%
“…Nevertheless, Israeli researchers claim that the occurrence of acute hepatitis A in a pregnant woman is associated with high rates of gestational complications and premature delivery [41]. A few cases of mother-to-child transmission of hepatitis A that is responsible for neonatal hepatitis or in utero complications [42,43] have also been published, but which we have not explored and which could be a subject of future research.…”
Section: Prevalence Of Hav Antibodies and Risk Factorsmentioning
confidence: 96%